Flowering in Xanthium strumarium: INITIATION AND DEVELOPMENT OF FEMALE INFLORESCENCE AND SEX EXPRESSION - Leonard, Maggy (1981)
Vegetative plants of Xanthium strumarium L. grown in long days were induced to flower by exposure to one or several 16-hour dark periods. The distribution of male and female inflorescences on the flowering shoot was described, and a scoring system was designed to assess the development of the female inflorescences. The time of movement of the floral stimulus out of the induced leaf and the timing of action of high temperature were shown to be similar for both the apical male and lateral female inflorescences. Strong photoperiodic induction of the plants favored female sex expression, while maleness was enhanced by exogenous gibberellic acid. The problem of the control of sex expression in Xanthium is discussed in relation to the distribution pattern of male and female inflorescences on the flowering shoot and to the state of the meristem at the time of the arrival of the floral stimulus.